Divergence or Convergence? South Africa's post-apartheid foreign policy and corporate expansion in Africa : the cases of Shoprite Holdings Limited and Standard Bank of South Africa Limited - Nshimbi, Christopher Changwe (University of Pretoria, 2021)
Thesis (PhD (Political Science))--University of Pretoria, 2021.